ANALYSIS OF APPROACH AND TAKE-OFF TECHNIQUES IN THE LONG JUMP AMONG JUNIOR HIGH SCHOOL STUDENTS - Hajirah; Afrizal; Fakhrur Rizal (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This classroom action research aims to improve the mastery of long service techniques in badminton through the This study aims to provide a detailed analysis of the approach run and take-off techniques in the long jump among eighth-grade students at SMP Negeri 1 Badar. Employing a quantitative descriptive methodology, the research utilized direct skill tests and systematic observation to gather data from a purposive sample of 20 students. The collected data were analyzed using SPSS version 20.0, with descriptive statistics revealing the central tendencies and frequency distributions of the performance scores. The findings indicate that the students' proficiency in both the approach and take-off techniques falls within a moderate category. Consequently, the overall performance in the long jump, measured by the distance achieved, was also classified as moderate. These results underscore a significant gap in the students' mastery of fundamental biomechanical principles essential for a successful jump. The study concludes by proposing targeted recommendations for Physical Education (PE) teachers and curriculum developers. These include the integration of more structured, technique-focused training regimens, the adoption of varied teaching methods to enhance student engagement and understanding, and the provision of adequate facilities to support effective skill acquisition. This research contributes to the broader effort of improving athletic pedagogy in the Indonesian junior high school context.